PENGARUH TERAPI AKTIVITAS KELOMPOK STIMULASI PERSEPSI TERHADAP GANGGUAN FUNGSI KOGNITIF PADA LANSIA (Study Quasy Experiment Di Unit Pelaksana Teknis Pelayanan Sosial Lanjut Usia Jombang di Kediri Tahun 2010) - Yektiningsih, Erwin (Akademi Keperawatan Pamenang, 2011)
Impaired cognitive function is a major mental health problems and confusion in the elderly, which of course has consequences for all daily activities. Impaired cognitive function can be assessed by the Mini Mental State Examination and one of therapies to maintain cognitive function is the Activity Group Therapy: Perception Stimulation, although it must be balanced with the fulfillment of nutritional and environmental orientation. This research uses quasi experiment design with pre and post test design. The population was 90 elderly, and 14 elderly was been the sample which choose with simple random sampling technique, the instrument used to cognitive function is The Mini Mental State Examination by the number of 30 questions to interview technique and observation while The Activity Therapy of Perceptive Stimulation Group is as many as 3 sessions with observation checklist technique. To know The Influence of Activity Therapy of Perceptive Stimulation Group to upset of cognitive function of the advanced ages, it uses Willcoxon statistic test and SPSS 11 For Windows. As the research result of Pre Test Mini Mental State Examination of 42,9 %, some do not undergo cognitive function but some do in middle, and 14,3 % undergo heavy cognitive function. The result of Activity Therapy of Perceptive Stimulation Group, 50 % has evaluation result with enough criteria, while 14,3% has evaluation result with criteria less. And The Post Test of Mental State Examination, 57,1 % do not undergo cognitive function upset, while 42,9% undergo middle cognitive function upset. Willcoxon statistic test has found the result that (Ï= 0,017) > (Î±=0,05). It means that H0 is refused and H1 is accepted. Automatically, The Influence of Activity Therapy of Perceptive Stimulation Group To Upset of Cognitive Function of The Advanced Ages in Team Work Unit of Social Service Technique Advanced Ages in Jombang in Kediri on 2010 has totally been found.Â If this therapy goes on routinely and maximally, it will defend the cognitive function of the advanced ages. The roles of the nurse in this therapy are as the leader, co-leader, facilitator, and observer.